2021
DOI: 10.37284/ijar.3.1.301
|View full text |Cite
|
Sign up to set email alerts
|

Beekeeping Potential, Richness, and Distribution of Plant Species Foraged by Stinging Honey Bee (Apis Mellifera L.) in West Kilimanjaro Tanzania Forest Service Agency (TFS) Plantation.

Abstract: An assessment of beekeeping potential, richness, and distribution of plant species foraged by stinging honey bee Apis mellifera L. in West Kilimanjaro Tanzania Forest Service Agency (TFS) Plantation area was conducted in 2020. A total of 40, 20 m x 20 m plots were set on the 5 natural vegetation remnants within the plantation forest ranges of Sanya juu, Lemosho, Hill wood, Wasendo, and Londrosi at an interval of 100 m. Within the 20 m x 20 m, 1 m x 1 m nested plots were established to assess herbs, sedge, gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The estimated production potential of bee products is about 138,000 tons of honey and 9,200 tons of beeswax per annum (ITC, 2015). In Africa, Tanzania is the secondlargest honey producer, after Ethiopia, and the tenth globally (Nyatsande et al, 2014;Ismail et al, 2021).…”
Section: 1beekeeping In Tanzaniamentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated production potential of bee products is about 138,000 tons of honey and 9,200 tons of beeswax per annum (ITC, 2015). In Africa, Tanzania is the secondlargest honey producer, after Ethiopia, and the tenth globally (Nyatsande et al, 2014;Ismail et al, 2021).…”
Section: 1beekeeping In Tanzaniamentioning
confidence: 99%
“…Despite the existing production potential in the beekeeping industry in Tanzania bee colonies are still less productive. Different studies (Tutuba & Vanhaverbeke, 2018;Ismail et al, 2021) indicated that productivity is still low and beekeeping markets are still under-served (ITC, 2015;Vanhaverbeke et al, 2021). That is, there is a lower yield per colony than predicted by scientists (MMA, 2012;Tutuba, 2021b).…”
Section: Beekeeping Productivity In Tanzaniamentioning
confidence: 99%